1999
DOI: 10.1086/306590
|View full text |Cite
|
Sign up to set email alerts
|

FexviiSoft X‐Ray Lines: Theory and Data Comparisons

Abstract: Fe XVII soft X-ray spectral emission lines are examined using data from the Flat Crystal Spectrometer (FCS) on the Solar Maximum Mission satellite. Results are compared with theoretical calculations and with other recent observational results. Disparate Ðndings from di †erent studies on the inferred opacity of the bright resonance line at 15.01 and on its center-to-limb behavior are reviewed. Present limi-A tations on the use of resonance scattering to infer coronal plasma densities and absolute elemental abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 19 publications
3
55
1
Order By: Relevance
“…Several investigations of solar active region and flare spectra in the 15-17 Å region indicate anomalously low observed line fluxes in strong transitions of Fe xvii, compared to the values predicted assuming effectively thin, coronal conditions. For example, Saba et al (1999) analyzed Flat Crystal Spectrometer data from SMM and Fig. 14.-Temperatures from helium-like triplet ratios in the Chandra quiescent spectra, tabulated for different electron densities (from Porquet et al 2001). Observed values of the ratios are dotted lines; 1 error bars are full lines.…”
Section: Optical Depths Of the Coronal Plasmamentioning
confidence: 99%
“…Several investigations of solar active region and flare spectra in the 15-17 Å region indicate anomalously low observed line fluxes in strong transitions of Fe xvii, compared to the values predicted assuming effectively thin, coronal conditions. For example, Saba et al (1999) analyzed Flat Crystal Spectrometer data from SMM and Fig. 14.-Temperatures from helium-like triplet ratios in the Chandra quiescent spectra, tabulated for different electron densities (from Porquet et al 2001). Observed values of the ratios are dotted lines; 1 error bars are full lines.…”
Section: Optical Depths Of the Coronal Plasmamentioning
confidence: 99%
“…7, where the different ratios can be recognized. In order to compare our measurements with solar measurements we include the solar measurements from Saba et al (1999) in the form of shaded areas in Figs. 3 and 4.…”
Section: Fe XVII Line Ratiosmentioning
confidence: 99%
“…They found differences between theoretical and observed values of the temperature sensitive G-ratio ( f + i)/r (Gabriel & Jordan 1969) and interpreted these differences as being due to resonant scattering effects. Schmelz et al (1997) and Saba et al (1999) measured five different line ratios and found significant optical depths only for the Fe  line at 15.03 Å ( 1 S 0 → 1 P 1 with a high oscillator strength f = 2.66). They compared the 15.03 Å line flux with line flux measurements for Fe  lines with lower oscillator strengths, namely two intercombination lines 1 S 0 → 3 D 1 at 15.27 Å with f = 0.593 and 1 S 0 → 3 P 1 at 16.78 Å with f = 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…2e and f. In stellar coronal observations there is a large discrepancy of their line intensities, relative to that of the 3d−2p transitions, between the observations and theoretical predictions for Fe XVII−XIX (Desai et al 2005). Some authors (Schrijver et al 1994;Schmelz et al 1997;Saba et al 1999;Mewe et al 2001) explain this as being due to stronger opacities in observations of stellar coronae for these strong 3d−2p transitions than for transitions with small g f -values. Here (see Fig.…”
Section: Chandra Letg Observationmentioning
confidence: 95%